2021
DOI: 10.3390/min12010025
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Energy Properties and Failure Process of Thermal Shock Treated Sandstone Subjected to Coupled Dynamic and Static Loads

Abstract: Thermal shock (TS) is known as the process where fractures are generated when rocks go through sudden temperature changes. In the field of deep rock engineering, the rock mass can be subjected to the TS process in various circumstances. To study the influence of TS on the mechanical behaviors of rock, sandstone specimens are heated at different high temperatures and three cooling methods (stove cooling, air cooling, and freezer cooling) are adopted to provide different cooling rates. The coupled dynamic and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the research of Li [17] et al, the energy calculation was used to explain the law of energy dissipation density under different strain rates for cemented backfill. Li et al [18] found a correlation between the various patterns of energy dissipations and the development of microcracks. In the study of Zhang et al [19], the energy dissipation density as an important parameter of the damage variable can better express the dynamic stress-strain relationship of sandstones under real-time high temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…In the research of Li [17] et al, the energy calculation was used to explain the law of energy dissipation density under different strain rates for cemented backfill. Li et al [18] found a correlation between the various patterns of energy dissipations and the development of microcracks. In the study of Zhang et al [19], the energy dissipation density as an important parameter of the damage variable can better express the dynamic stress-strain relationship of sandstones under real-time high temperatures.…”
Section: Introductionmentioning
confidence: 98%